Florida Springs Land Use Information Tool - Thomas Obreza (EDIS)
The purpose of this publication is to provide information about how land use influences the amount of nitrogen that may be imported as fertilizers or soil amendments, the amount of nitrogen that may be exported in the harvested portion of a crop, the amount of water that may be consumed, and the relative pesticide loading. This document is CIR 1448, a circular of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2004.